David Miller and Rationality without “Good Reasons”? Criticism of Miller’s Interpretation of Critical Rationalism - Havlík, Vladimír (Teorie vědy / Theory of Science, 2018)
David Miller in his books Critical Rationalism (1994) and Out of Error (2006), as one of the few Popper’s students, tries not only to explain and defend Popper’s critical rationalism but also to develop it further. Miller’s restatement of critical rationalism, however, assumes that no “good reason,” but only arguments are needed for rational action. Th is article focuses precisely on this question of the existence of the so-called “good reasons” in connection with rationality and rational decision-making and shows that Miller’s demand for the absence of “good reasons” is not only too radical but also unacceptable in terms of Popper’s or Musgrave’s concepts of critical rationalism.